A new cognitive behavior therapy for adolescents with avoidant/restrictive food intake disorder in a day treatment setting: A clinical case series. Issue 4 (25th February 2019) - Dumont, Eric; Jansen, Anita; Kroes, Diana; de Haan, Eline; Mulkens, Sandra
Abstract: Objective: Avoidant/restrictive food intake disorder (ARFID) is a new diagnosis in the DSM‐5 Feeding and Eating Disorders section, for which very limited treatment research has been carried out, yet. A new, 4‐week exposure based cognitive behavioral therapy (CBT) day treatment, which integrated the inhibitory learning principles, was developed for adolescents with ARFID, and tested in the current study. Method: A nonconcurrent multiple baseline design was used in a clinical case series of eleven 10‐ to 18‐year‐old patients. After baseline, the 4‐week CBT followed. Measurements of DSM‐5 ARFID diagnosis, food neophobia and related measures such as body weight and length, were taken at baseline (t1), at the end of the 4‐week intensive day treatment (t2) and 3 months after treatment (follow‐up, t3). A food selectivity test, a 1‐week food diary, and behavioral measures on food intake were also taken at baseline and at 3‐month follow‐up. Furthermore, continuous measurements of believability of dysfunctional cognitions, anxiety, and food acceptance were taken throughout the 4‐weeks day treatment. Results: At follow‐up, 10 out of 11 patients were in remission and had a healthy body weight and an average, age‐adequate nutritional intake. For most patients, food neophobia scores decreased to a nonclinical range. The belief in dysfunctional cognitions and anxiety levels decreased during treatment. Discussion: This new exposure‐based CBT for adolescents with ARFID seems promising. These results may be very useful for clinical practice and stimulate further development of effective CBT interventions in the area of ARFID.